Are Teams Less Inequality Averse than Individuals? - Haoran He; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2014)
We compare inequality aversion in individuals and teams by means of both within- and between-subject experimental designs, and we investigate how teams aggregate individual preferences. We find that team decisions reveal less inequality aversion than individual initial proposals in team decision-making. However, teams are no more selfish than individuals who decide in isolation. Individuals express strategically more inequality aversion in their initial proposals in team decision-making because they anticipate the selfishness of other members. Members with median social preferences drive team decisions. Finally, we show that social image has little influence because guilt and envy are almost similar in anonymous and non-anonymous interactions.
Keywords: C91; C92; D03; D63; D72; 330; team; inequity aversion; preference aggregation; social image; experiment